Design and implementation of a linear X-Y table drive system based on TMS320F2812 DSP controller - 黃品鈞 (2004)
碩士 === 南台科技大學 === 電機工程系 === 92 === In this thesis, a DSP-based drives system for a linear X-Y table composed by two sets of permanent magnet linear synchronous motor (PMLSM) is presented. The TMS320F2812 DSP chip, which is a new generation product of Texas Instruments, with the characteristics of fast computation capability (150MIPS), up to 128Kx16 flash and the complete motor control peripheral which includes 2 set (12 lines) of PWM output, 2 set (4 lines) of QEP input, 12 channels 12-bit A/D converter (200ns conversion time), 56 bits GPIO, is very suitable to develop a high performance two-axis servo motion controller system. Therefore, a fully digital servo controller for a linear X-Y table, which includes two sets of current vector control scheme, two sets of SVPWM generation, two sets of A/D conversion, two sets of coordinate transformation, two sets of QEP detection, two sets of position and speed controller strategy, a motion trajectory control etc. can be realized by software in a single DSP chip. For increasing the performance of PMLSM drives, the thesis also proposes an adaptive fuzzy controller constructed by fuzzy basis function and a parameter adjustable mechanism in position control loop, to cope with the system uncertainty and pay-load disturbance and to increase a fast tracking response. To confirm the effectiveness of the proposed system, an experimental system included by an X-Y PMLSM table, a TMS320F2812 DSP control board, inverters, rectifiers have been set up and some experimental results have been validated the theoretical ones.